PERANCANGAN PROMOSI LALITO COFFEE MELALUI MEDIA IKLAN TV - M.HARRY OFINDRA, Dr. Budiwirman, M.Pd. San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Company lalito coffee trying to promoting the product expected can reach objective that is more broadly , but a promotion all this do only use the virtual world for example through twitter and instagram.Election television commercial is a media promotion an effective and efficient because it could show how performance and the layout lalito and give typical its own so that the public can get to know and understand lalito coffee , for the purpose of establishing media promotion related of the company lalito coffee with the approach based audio visual be a pleasant new to promote.In the design this television commercial in need primary and secondary data then the data that has been in learned in analysis using a method of training .Design produce mainstream media of television commercial lasts a minute thirty-two seconds in a dvd format showing impressions the atmosphere and process of making coffee. Television commercial use visualize scene promotion with about the procedure of making coffee .Media promotion main furnished media supporting among other posters , stickers , the calendar , guest comment , name card , x banner , menu , leaflets , flayer , catalog and cd label.Password: design , lalito coffee , television commercial .